GENDER DIFFERENCES IN TRAFFIC RISK BEHAVIOR AMONG MOTORCYCLISTS IN INDONESIAN CITY - Anggraini, Renni; Mauliana, Risma; Kumala, Tasya; Fadhly, Noer (Journal of Applied Engineering Science, 2023)
Several factors, such as humans, vehicles, roads, and the environment, can cause traffic accidents. However, studies have shown that the crucial problem in traffic accidents is the human factor, in particular motorcycle users, or motorcyclists. This study aimed to investigate the traffic risk behavior of motorcyclists’ considering gender as a factor to reduce traffic accidents. The data was obtained through a self-administered questionnaire completed by 155 motorcyclists in Aceh Province, Indonesia, specifically in Banda Aceh City and the neighboring areas. The questionnaire included information about the characteristics of the respondents as well as their perceptions of traffic risks. The data collected were analyzed using Chi-Square test/Fisher’s Exact Test, and Odds Ratio (OR). According to the findings, gender had no significant effect on motorcyclists' traffic risk behavior among the eight variables considered (overtaking, speeding, the use of cell phone, turning without signal alert, tailgating, the use of helmet, helmet strapping, and the use of protective cloth). Subsequently, it was observed that not using helmets while riding put men at greater risk than women. The odds ratio of 3.930 implies that men who frequently drive without helmets have a 3.930 times higher risk of traffic accidents than women. The study revealed that, although gender did not affect traffic risk behavior, men were more at risk than women in almost all categories except tailgating. As a result, male motorcyclists are required to be more responsible when driving, and local governments must play a key role in law enforcement to decrease traffic accidents.
Keywords: motorcyclists, traffic risk, gender, road safety